Device complications with addition of defibrillation to cardiac resynchronisation therapy for primary prevention. Issue 18 (14th March 2018) - Barra, Sérgio; Providência, Rui; Boveda, Serge; Duehmke, Rudolf; Narayanan, Kumar; Chow, Anthony W; Piot, Olivier; Klug, Didier; Defaye, Pascal; Gras, Daniel; Deharo, Jean-Claude; Milliez, Paul; et al.
Abstract : Objective: In patients indicated for cardiac resynchronisation therapy (CRT), the choice between a CRT-pacemaker (CRT-P) versus defibrillator (CRT-D) remains controversial and indications in this setting have not been well delineated. Apart from inappropriate therapies, which are inherent to the presence of a defibrillator, whether adding defibrillator to CRT in the primary prevention setting impacts risk of other acute and late device-related complications has not been well studied and may bear relevance for device selection. Methods: Observational multicentre European cohort study of 3008 consecutive patients with ischaemic or non-ischaemic dilated cardiomyopathy and no history of sustained ventricular arrhythmias, undergoing CRT implantation with (CRT-D, n=1785) or without (CRT-P, n=1223) defibrillator. Using propensity score and competing risk analyses, we assessed the risk of significant device-related complications requiring surgical reintervention. Inappropriate shocks were not considered except those due to lead malfunction requiring lead revision. Results: Acute complications occurred in 148 patients (4.9%), without significant difference between groups, even after considering potential confounders (OR=1.20, 95% CI 0.72 to 2.00, p=0.47). During a mean follow-up of 41.4±29 months, late complications occurred in 475 patients, giving an annual incidence rate of 26 (95% CI 9 to 43) and 15 (95% CI 6 to 24) per 1000 patient-years in CRT-D and CRT-P patients, respectively. CRT-D was independently associated with increased occurrence of late complications (HR=1.68, 95% CI 1.27 to 2.23, p=0.001). In particular, when compared with CRT-P, CRT-D was associated with an increased risk of device-related infection (HR 2.10, 95% CI 1.18 to 3.45, p=0.004). Acute complications did not predict overall late complications, but predicted device-related infection (HR 2.85, 95% CI 1.71 to 4.56, p<0.001). Conclusions: Compared with CRT-P, CRT-D is associated with a similar risk of periprocedural complications but increased risk of long-term complications, mainly infection. This needs to be considered in the decision of implanting CRT with or without a defibrillator.